2015
DOI: 10.1175/jcli-d-14-00271.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Energy and Mass Fluxes Controlling Godthåbsfjord Freshwater Input in a 5-km Simulation (1991–2012)*,+

Abstract: Freshwater runoff to fjords with marine-terminating glaciers along the Greenland Ice Sheet margin has an impact on fjord circulation and potentially ice sheet mass balance through increasing heat transport to the glacier front. Here, the authors use the high-resolution (5.5 km) HIRHAM5 regional climate model, allowing high detail in topography and surface types, to estimate freshwater input to Godthåbsfjord in southwest Greenland. Model output is compared to hydrometeorological observations and, while simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(135 citation statements)
references
References 60 publications
3
132
0
Order By: Relevance
“…Recent hydrological simulations estimate the annual freshwater input to Godthåbsfjord (excluding solid ice discharge as well as submarine melt from glaciers) to be 22.5±5.2 km 3 yr −1 for the period 1991-2012 (Langen et al, 2014). Ice sheet runoff accounts for 60 % of the freshwater input, land runoff is responsible for 34 %, and net precipitation over the fjord surface represents the remaining 6 % (Langen et al, 2014). project a similar estimate of 10-20 km 3 glacial ice loss per year (solid ice discharge, surface ice melt and submarine melt) for the Godthåbsfjord glaciers.…”
Section: Field Sitementioning
confidence: 99%
“…Recent hydrological simulations estimate the annual freshwater input to Godthåbsfjord (excluding solid ice discharge as well as submarine melt from glaciers) to be 22.5±5.2 km 3 yr −1 for the period 1991-2012 (Langen et al, 2014). Ice sheet runoff accounts for 60 % of the freshwater input, land runoff is responsible for 34 %, and net precipitation over the fjord surface represents the remaining 6 % (Langen et al, 2014). project a similar estimate of 10-20 km 3 glacial ice loss per year (solid ice discharge, surface ice melt and submarine melt) for the Godthåbsfjord glaciers.…”
Section: Field Sitementioning
confidence: 99%
“…Compared with the HIRHAM5 version described in Christensen et al (2006), a dynamic snow/ice scheme together with an updated snow/ice albedo scheme have been included in the model runs used in this study (see Langen et al 2015Langen et al , 2017 for details). (b, bottom).…”
Section: Modelsmentioning
confidence: 99%
“…A comparison of the performance of early versions of these RCMs in Rae et al (2012) showed some differences in performance. However, analysis by Mottram et al (2017) and Vernon et al (2013) shows that these RCMs produce similar values for surface mass balance over the ice sheet as a whole, although with some significant differences in the components of mass balance and in the spatial distribution of these components (e.g., Langen et al 2015;Van As et al 2014), partly attributable to different model resolution as well as different ice masks and potentially different parameterization schemes. Here, we focus on validating the HIRHAM5 simulations against observations, excluding a comparison with previous high-resolution downscalings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations